Evaluation of management-dependent changes in the water regime of extensive grasslands - Renata Duffková (Soil and Water Research, 2008)
The origin of the differences in the water regime components of 0-0.6 m soil profile was identified in extensively managed permanent grasslands (PG, variants: once cut - 1C, twice cut - 2C, nocut - NC, mulched June - MVI, mulched July - MVII) using the method of the soil water balance (drainage lysimeters). The differences in the water regime of the experimental variants manifested themselves depending on adequate soil water storage in the period when the amounts of transpiring biomass in individual variants differed markedly: (i) at the beginning of the vegetation period, when the surface litter in the NC and 1C variants reduced the actual evapotranspiration (ETA), (ii) at the time of mowing and mulching (M), when these treatments (mainly M) increased the soil water supply by ca 10-20 mm per month and decreased the ETA values by 1-2.5 mm per day for about 2-4 weeks as compared to non-mown variants on the given date, and (iii) as a result of the presence of different agrobotanical groups with distinct transpiration intensity (leguminous plants with a higher transpiration intensity in the 2C variant compared to grasses). The post-M reduction in evaporation was compensated by a higher total transpiration resulting from an increase in the aboveground phytomass. The lowest water consumption with the highest supply to the groundwater resources was recorded in the NC and 1C variants. The 2C variant containing leguminous plants with high water requirements had the highest consumption of water for evaporation and the lowest amount of water runoff from the soil profile. The identification of the water regime differences in individual variants helped determine the appropriate PG management with the aim to increase the underground water levels in the protection zones of water resources. The 1C variant of management is recommended mainly in the source areas of groundwater with lower productivity soils. In the accumulation areas of water resources (floodplain areas) with a deep soil profile and highly productive grassland, the 2C variant is required; mulching, which would largely support the yielding capacity of grassland, should be avoided. Mulching may occasionally be used as a relatively suitable method for the sites with a low yielding capacity in the source area.